Consumer Perception of Fast Fashion: Analysis of The Role of Environmental Knowledge And Monetary Benefits In Purchase Intention Using The Theory of Planned Behavior - Malik, Agil Reza; Lubis, Ratna Lindawati (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
The fast fashion industry has experienced dramatic growth over the past two decades, driven by the rapid supply and affordable prices. This phenomenon has led to overconsumption and the accumulation of textile waste, contributing to land, marine, and air pollution. The expansion of the fast fashion industry also poses a significant threat to Indonesia due to the substantial growth in both producers and consumers. Consumer environmental awareness is a critical factor in promoting sustainability, necessitating an analysis of the factors influencing fast fashion purchase intentions. However, Indonesia currently lacks fixed regulations to curb fast fashion production. Therefore, this study examines the influence of environmental knowledge and monetary benefits, utilizing the Theory of Planned Behavior to predict fast fashion purchase intentions in Indonesia. A quantitative survey method was employed, targeting fast fashion consumers in Indonesia. Data from 134 valid respondents were analyzed using the SEM-PLS method. Of the 12 hypotheses tested, seven were supported. The findings indicate that environmental knowledge significantly influences perceived behavioral control, while monetary benefits positively affect brand attitude and subjective norms. However, monetary benefits have a negative impact on perceived betrayal. Monetary benefits are important for Indonesian consumers in forming positive attitudes and subjective norm pressures to purchase fast fashion products. Perceived betrayal in fast fashion negatively affects purchase intentions. The study reveals that Indonesian consumers exhibit low environmental knowledge and lack feelings of disappointment toward fast fashion. Consequently, the government should enhance environmental knowledge through clothing recycling initiatives and establish policies to restrict fast fashion purchases. Keywords— environmental knowledge; fast fashion; monetary benefits; perceived betrayal; theory planned behavior